Effect of electric heating and ice added to the bowl on mainstream waterpipe semivolatile furan and other toxicant yields. (21st September 2019) - Brinkman, Marielle C; Teferra, Andreas A; Kassem, Noura O; Kassem, Nada OF
Abstract : Objectives: We examined mainstream total particulate matter, nicotine, cotinine, menthol, pyrene, carbon monoxide (CO) and semivolatile furan yields from a commercial waterpipe with two methods for heating the tobacco, quick-light charcoal (charcoal) and electric head (electric) and two water bowl preparations: with (ice) and without ice (water). Methods: Emissions from a single brand of popular waterpipe tobacco (10 g) were generated using machine smoking according to a two-stage puffing regimen developed from human puffing topography. Tobacco and charcoal consumption were calculated for each machine smoking session as mass lost, expressed as a fraction of presmoking mass. Results: The heating method had the greatest effect on toxicant yields. Electric heating resulted in increases in the fraction of tobacco consumed (2.4 times more, p<0.0001), mainstream nicotine (1.4 times higher, p=0.002) and semivolatile furan yields (1.4 times higher, p<0.03), and a decrease in mainstream CO and pyrene yields (8.2 and 2.1 times lower, respectively, p<0.001) as compared with charcoal. Adding ice to the bowl resulted in higher furan yields for electric heating. Menthol yields were not different across the four conditions and averaged 0.16±0.03 mg/session. 2-Furaldehyde and 5-(hydroxymethyl)−2-furaldehyde yields were up to 230 and 3900 times higher, respectively, than those reported for cigarettes. Conclusion: Waterpipe components used to heat the tobacco and water bowl preparation can significantly affect mainstream toxicant yields. Mainstream waterpipe tobacco smoke is a significant source of inhalation exposure to semivolatile furans with human carcinogenic and mutagenic potential. These data highlight the need for acute and chronic inhalation toxicity data for semivolatile furans and provide support for the establishment of limits governing sugar additives in waterpipe tobacco and educational campaigns linking waterpipe tobacco smoking behaviours with their associated harm.